2017
DOI: 10.26838/medrech.2017.4.6.360
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Cancer and its Aetiology in Sub-saharan Africa: A Literature Review

Abstract: Cervical cancer represents a huge burden of non-infectious disease globally. It is the second commonest cancer in the female. There are over half a million deaths recorded every year as result of cervical cancer. The aetiological agent implicated in this disease is the human Papillomavirus. The high-risk human papillomavirus has been mostly implicated. The commonest high-risk human papillomavirus implicated in cervical cancer worldwide is type 16 and 18. The viral infection of the uterine cervical epithelium i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 20 publications
1
0
0
Order By: Relevance
“…Nigeria is among the countries with a high burden of viral hepatitis with a Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) prevalence of 11% and 2.2%, respectively [28]. This study revealed that majority of the scavengers in the study are in the age bracket 21-30 years which is 45.4% that is in agreement with Irabor et al [29] which concluded that the highest population of scavengers i.e., 36% are in the age bracket 20 -29 years and Isaac et al [30] stated that majority 35.42% of respondents are between 18-28 years. In terms of education, majority of wastes scavengers in Kwara state all to the category of primary school leavers as the constitute 38.8% of total respondents and closely followed by those without any formal education which constitute Senatorial districts a higher educational certificate.…”
Section: Discussionsupporting
confidence: 87%
“…Nigeria is among the countries with a high burden of viral hepatitis with a Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) prevalence of 11% and 2.2%, respectively [28]. This study revealed that majority of the scavengers in the study are in the age bracket 21-30 years which is 45.4% that is in agreement with Irabor et al [29] which concluded that the highest population of scavengers i.e., 36% are in the age bracket 20 -29 years and Isaac et al [30] stated that majority 35.42% of respondents are between 18-28 years. In terms of education, majority of wastes scavengers in Kwara state all to the category of primary school leavers as the constitute 38.8% of total respondents and closely followed by those without any formal education which constitute Senatorial districts a higher educational certificate.…”
Section: Discussionsupporting
confidence: 87%